The hope of liberation in world religions - De la Torre, Miguel A. (Baylor University Press, 2008)
Liberation theology emphasizes the Christian mission to bring justice to the poor and oppressed. As a part of Christian theology, liberation theology has been most frequently associated with the Catholic Church in Latin America. This groundbreaking work seeks to identify how the theological concepts of liberation theology might be manifested within other world faith traditions. This is thus the first book that attempts to find a ""common ground"" for liberation theology across religions. All of the contributors are scholars who share the religion or belief system they describe. Throughout, the